2014
DOI: 10.1016/j.neuroscience.2014.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Epileptiform synchronization and high-frequency oscillations in brain slices comprising piriform and entorhinal cortices

Abstract: We employed field potential recordings in extended in vitro brain slices form Sprague-Dawley rats containing the piriform and entorhinal cortices (PC and EC, respectively) to identify the characteristics of epileptiform discharges and concomitant high-frequency oscillations (HFOs, ripples: 80-200Hz, fast ripples: 250-500Hz) during bath application of 4-aminopyridine (4AP, 50μM). Ictal-like discharges occurred in PC and EC either synchronously or independently of each other; synchronous ictal discharges always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…We have confirmed here that ionotropic glutamatergic receptor-mediated signaling is required for the generation of ictal discharges in both PC and EC (Avoli et al, 2013;Hamidi et al, 2014;Herrington et al, 2014). In keeping with evidence obtained in these previous studies, we have found that blockade of glutamatergic signaling using NMDA and non-NMDA receptor antagonists led to the occurrence of isolated, slow GABA receptordependent potentials during application of 4AP.…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andsupporting
confidence: 91%
See 3 more Smart Citations
“…We have confirmed here that ionotropic glutamatergic receptor-mediated signaling is required for the generation of ictal discharges in both PC and EC (Avoli et al, 2013;Hamidi et al, 2014;Herrington et al, 2014). In keeping with evidence obtained in these previous studies, we have found that blockade of glutamatergic signaling using NMDA and non-NMDA receptor antagonists led to the occurrence of isolated, slow GABA receptordependent potentials during application of 4AP.…”
Section: Modulation Of Isolated Gabaergic Events By Kcc2 Blockers Andsupporting
confidence: 91%
“…To identify oscillations in each frequency range (80-200 Hz and 250-500 Hz), a multi-parametric algorithm was employed using routines based on standardized functions (Matlab Signal Processing Tool-box) as described in detail in Hamidi et al (2014) and Salami et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously characterized 4AP-induced epileptiform discharges in PC and EC (Hamidi et al, 2014) and has reported the effects of neurosteroids on such epilepti-form activity and HFOs in the PC of healthy rats (Herrington et al, 2013). It remains however unknown whether these effects are maintained in the epileptic brain.…”
Section: Introductionmentioning
confidence: 99%